You say it‘s not me: the influence of offering external explanations of rejection and acceptance behavior on the perception of benevolence in borderline personality disorder - Schulze, Anna; Rommelfanger, Berit; Schendel, Elisabeth; Kammler-Sücker, Kornelius; Lis, Stefanie (Borderline Personality Disorder and Emotion Dysregulation, 2024)
Interpersonal impairments in patients diagnosed with borderline personality disorder (BPD) are characterized by the fear of being rejected and high levels of loneliness. Potential underlying factors are alterations in the processing of social interactions and the associated perceptions of social partners. In this regard, BPD patients tend to attribute the cause of negative rather than positive events to their own person and to perceive others as less trustworthy than healthy controls (HCs). To date, no study has investigated whether the effect of experimentally influenced causal attributions of social interactions on the perception of a social partner differs between BPD patients and HCs. A new virtual reality paradigm was developed to investigate the perception of benevolence following the induction of social rejection and acceptance, while experimentally manipulating whether an external cause for this behavior was provided. The data of 62 participants (32 HCs, 30 BPD patients) were analyzed using linear mixed-effects models. Associations of benevolence ratings with attributional style, rejection sensitivity, self-esteem, childhood trauma, and loneliness were investigated via correlational and multiple linear regression analyses. Across both groups, a social partner was rated as less benevolent following rejection than following acceptance. An external explanation mitigated this negative effect of rejection. Overall, benevolence ratings were lower in BPD patients than in HCs. This group difference was stronger following acceptance than following rejection. Independent of acceptance and rejection, an external explanation was associated with a higher level of benevolence only in the HC group. No associations of the effects of the experimental conditions with attributional style, childhood trauma, rejection sensitivity, self-esteem, or loneliness were found. Our findings indicate that acceptance and provided external explanations for rejection have a less positive impact on the perception of a social partner’s attitude toward oneself in BPD patients than in HCs. More research is needed to identify predictors of benevolence perception and which steps of social information processing are altered. The therapeutic implications include the importance of strengthening the perception and enjoyment of being accepted as well as improving the mentalizing ability of BPD patients.
Gesehen am 14.04.2025